“Um mundo assombrado por demônios” : a história da descoberta e desenvolvimento dos antibióticos - Mota, Ana Carolina Almeida Lima (2023)
This work is a bibliographical research on the evolution of antibiotics as well as an analysis of the world before and after its discovery, regarding the field of pharmacy and medicine. In a world that was isolated by microbial diseases that caused mass deaths, having a substance that brought healing was a huge milestone. It is known that the most devastating epidemic that has devastated humanity, the Black Death, killed between 75 and 200 million people during the 19th century, which translates into a percentage between 30 and 60% of the European population. In this context, it is evident that the losses were great untilwe reached the discoveries. To understand current health aspects, as well as all the diseases and treatments used today, especially when it comes to bacterial diseases, it is essential to study and analyze history. Therefore, this course completion work aims to understand society before and after the discovery of thedrugs that brought life to the world and revolutionized pharmacy, as well as its development.